APLIKASI PUPUK CAIR ORGANIC BOOST TERHADAP HASIL Asystasia gangetica (L.) subsp. Micrantha - D.P.J. Jayantara; N.N.C. Kusumawati; N.M. Witariadi (Fakultas Peternakan Universitas Udayana, 2025)
Asystasia igangetica ihas ipotential ias ia ihigh-quality iforage icrop; ihowever, iits icultivation irequires iadditional inutrients ithrough ifertilization ito iimprove iplant iproductivity. iThis istudy iaimed ito idetermine ithe ieffect iof iliquid iorganic ifertilizer “Organic iBoost” ion ithe iyield iof iAsystasia igangetica i(L.) isubsp. iMicrantha. iThe iresearch iwas iconducted iin ia igreenhouse ilocated iin iSading iVillage, iBadung iRegency, iBali iProvince, ifor i12 iweeks, ifrom iApril i20 ito iJune i20, i2025. iThe iexperiment iused ia icompletely irandomized idesign i(CRD) iconsisting iof ifive ifertilizer idosage itreatments: iD0 i(0 il iha-1), iD1 i(2.500 il iha-1), iD2 i(5.000 il iha-1), iD3 i(7.500 il iha-1), idan iD4 i(10.000 il iha-1), ieach ireplicated isix itimes. iThe iobserved ivariables iincluded ileaf idry iweight, istem idry iweight, itotal iforage idry iweight, ithe iratio iof ileaf ito istem idry iweight, iand ithe iratio iof ileaf ito itotal iforage idry iweight. iThe iresults ishowed ithat ithe iapplication iof iliquid iorganic ifertilizer “Organic iBoost” iat ia idosage iof i10.000 il iha-1 i iproduced ihigher ivalues ifor ileaf idry iweight, istem idry iweight, iand itotal iforage idry iweight icompared ito iother itreatments, ialthough ithe idifferences iwere inot istatistically isignificant i(P>0,05). iIn icontrast, ithe icontrol itreatment (0 il iha-1) iproduced islightly ihigher ivalues ifor ithe iratios iof ileaf ito istem idry iweight iand ileaf ito itotal iforage idry iweight, ibut ithe idifferences iwere ialso inot isignificant. iIt ican ibe iconcluded ithat ithe iapplication iof iliquid iorganic ifertilizer “Organic iBoost” idid inot isignificantly iincrease ithe iyield iof iAsystasia igangetica i(L.) isubsp. iMicrantha, ialthough ithe i10.000 il iha-1 idosage itended ito iprovide ithe ibest ioverall igrowth iresponse. ABSTRAK Asystasia igangetica iberpotensi isebagai ihijauan ipakan iberkualitas, inamun idalam ipengembangan itanaman iini imemerlukan itambahan iunsur ihara imelalui ipemupukan iuntuk imeningkatkan iproduktivitas itanaman. iPenelitian iini ibertujuan iuntuk imengetahui ipengaruh ipemberian ipupuk.cair iOrganic iboost iterhadap ihasil iAsystasia igangetica i(L.) isubsp. iMicrantha. iPenelitian iini idilaksanakan idi irumah ikaca, idi iDesa iSading, iKabupaten iBadung, iProvinsi iBali, iselama i12 iminggu idimulai idari itanggal i20 iApril i- i20 iJuni i2025. iPenelitian imenggunakan irancangan iacak ilengkap i(RAL) idengan ilima iperlakuan idosis ipupuk iOrganic iboost, iyaitu: i iD0 i(0 il iha-1), iD1 i(2.500 il iha-1), iD2 i(5.000 il iha-1), iD3 i(7.500 il iha-1), idan iD4 i(10.000 il iha-1), idan isetiap iperlakuan idiulang ienam ikali. iVariabel iyang idiamati, imeliputi: iberat ikering idaun, iberat ikering ibatang, iberat ikering itotal ihijauan, inisbah iberat ikering idaun idengan iberat ikering ibatang, idan inisbah iberat ikering idaun idengan iberat ikering itotal ihijauan. iHasil ipenelitian imenunjukkan ibahwa ipemberian ipupuk icair iOrganic iboost ipada iAsystasia igangetica i(L.) isubsp. iMicrantha ipada iperlakuan i10.000 il iha-1 imemberikan ihasil ilebih itinggi ipada iberat ikering idaun, iberat ikering ibatang, idan iberat ikering itotal ihijauan, inamun itidak iberbeda inyata, isedangkan iperlakuan i0 il iha-1 imenunjukan ihasil ilebih itinggi ipada ivariabel inisbah iberat ikering idaun idengan iberat ikering ibatang, idan inisbah iberat ikering idaun idengan iberat ikering itotal ihijauan, inamun iberbeda itidak inyata. iDapat idisimpulkan ibahwa ipemberian ipupuk icair iOrganic iboost ibelum imampu imeningkatkan ihasil iAsystasia igangetica i(L.) isubsp. iMicrantha idan idosis i10.000 il iha-1 ipupuk icair iOrganic iboost icendrung imemberikan ihasil iAsystasia igangetica i(L.) isubsp. iMicrantha ipaling ibaik.